2021
DOI: 10.1515/pteridines-2020-0025
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum homocysteine as a biomarker for early diagnosis of diabetic nephropathy in type 2 diabetes mellitus patients

Abstract: Objective The aim of this study was to investigate the clinical significance of serum homocysteine (Hcy) as a biomarker for early diagnosis of diabetic nephropathy (DN) in type 2 diabetes mellitus (T2DM) patients. Methods Fifty-five T2DM patients with DN and 51 T2DM patients without DN were prospectively recruited from January 2016 to May 2020 in our hospital. The serum Hcy was tested by electrochemiluminescence assay in DN a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Applying serum Hcy as the reference, the diagnostic sensitivity, specificity, and AUC were 84.31 (71.41–92.98) %, 74.55 (61.00–85.33) %, and 0.85 (0.78–0.92) %, respectively, with the cut-off value between DN and Type 2 DM groups is 12.08, serum Hcy can also be used as a serological marker for early diagnosis of DN with relatively high sensitivity and specificity. 32 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying serum Hcy as the reference, the diagnostic sensitivity, specificity, and AUC were 84.31 (71.41–92.98) %, 74.55 (61.00–85.33) %, and 0.85 (0.78–0.92) %, respectively, with the cut-off value between DN and Type 2 DM groups is 12.08, serum Hcy can also be used as a serological marker for early diagnosis of DN with relatively high sensitivity and specificity. 32 …”
Section: Resultsmentioning
confidence: 99%
“…Applying serum Hcy as the reference, the diagnostic sensitivity, specificity, and AUC were 84.31 (71.41-92.98) %, 74.55 (61.00-85.33) %, and 0.85 (0.78-0.92) %, respectively, with the cut-off value between DN and Type 2 DM groups is 12.08, serum Hcy can also be used as a serological marker for early diagnosis of DN with relatively high sensitivity and specificity. 32 b-trace protein b-trace protein (bTP), known as lipocalin prostaglandin D2 synthase (L-PGDS), is an emerging marker of GFR. It is also a low-molecular-weight glycoprotein that belongs to the lipocalin superfamily.…”
Section: Serum Homocysteinementioning
confidence: 99%
“…NRG4 may enhance the activity of brown adipose tissue, increase the expression of thermogenic markers, reduce the expression of lipogenic/adipogenic genes, aggravate the browning of white adipose tissue, promote the oxidation and ketogenesis of liver fat, induce neurite growth and enhance the blood vessels of adipose tissue, to prevent obesity and related metabolic complications [ 31 ]. Ye et al [ 13 ] found that the sensitivity, specificity and AUC of serum HCY level in the diagnosis of DN were 84.31%, 74.55% and 0.85, showing high sensitivity, specificity and AUC. In our study, HCY showed higher specificity and sensitivity in predicting DKD with more data samples.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 12 ] showed that serum HCY and Cys C levels were consistent with the occurrence and progression of DN, and serum HCY and Cys C were sensitive biomarkers for detecting early DN and monitoring its progression. Ye et al [ 13 ] found that serum HCY level in the DN group was higher than that in the T2DM group, which was associated with kidney damage, and could be used as a potential serological indicator for the early diagnosis of DN. In addition, a meta-analysis suggested that serum HCY was a promising biomarker of DN [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated an obviously elevated serum concentration of Hcy in patients with DN compared to the non-diabetic control group. The concentration was also significantly correlated with the severity of renal damage, and was proposed to be a serological marker for early DN diagnosis [ 21 ]. A study involving elderly Chinese type 2 diabetes patients found that serum Hcy concentrations were elevated and could potentially serve as a risk factor for diabetic kidney disease, although the serum concentration of Hcy was not considered to be a good biomarker [ 22 ].…”
Section: Discussionmentioning
confidence: 99%